Model Perancangan Pusat Komunitas Kampung Keparakan sebagai Antitesis Panti Asuhan: Fasilitas Reunifikasi Keluarga - Gilang Dwi Alridho; Kurnia Widiastuti (Universitas Sebelas Maret Surakarta, 2021)
Child institutionalization (orphanage) is considered as a crime due to child segregation from their family to a residential care institution. In Indonesia, about 94% of 500.000 children are still having at least one biological parent and they live in orphanages. There are several bad impacts in orphan mental health such as less confidence, indifferent, reserved, and suffering dramatic developmental delays. Therefore, there is a need to develop the design of a facility to reunite the orphans and their family as an act of deinstitutionalization. This facility context is integrated to and managed by (kampong) community center as a way to decentral and deinstitutionalize orphanages, which need the role of community as a mediator for orphans to reunite with their community and family. Since this article writes the research part as well as proposing a solution of design, inductive-abductive-deductive methods are used. According to data gathered and analyzed, main design problems formulated are how to design spaces (design of open space, counseling room, and integration to other facilities) that encourage family reunification. Therapeutic Courtyard is the design concept synthesized based on those problems. First strategy is to create a playground theme to a central courtyard as a tool to encourage family interaction. Second is a counseling room as space that provides a sense of relief. Third solution is putting natural elements as a space enclosure as well as creating therapeutic effects.